Faktor-Faktor yang Memengaruhi Realisasi Pembiayaan Mikro Syariah dan Dampaknya terhadap Omzet Usaha Nasabah: Studi Kasus KJKS BMT UGT Sidogiri Cabang Koja Jakarta - Nadiah Hidayati; Widyastutik; Ranti Wiliasih (AL-MUZARA'AH, 2014)
Micro-business has a role of the national economy development. However, micro scale entrepreneurs face problems of limited capital. This studyto analyze the factors affecting the amount of the financing provided BMT and their impact on bussiness turnover. This research was conducted in March-April at KJKS BMT UGT Sidogiri branch Koja Jakarta. This research used a purposive sampling technique with a total of 30 respondents. OLS analysis results proved thatbusiness aset, frequency financing, installment period, and dummy businesshave significantlyeffect on the realization of financing. Meanwhile, the factors affecting the customer’s turnover are business aset, amount of financing, business profit after financing, time duration of educational, time duration of business, and dummy business.